EFEKTIVITAS PENYELENGGARAAN ANALISIS DAMPAK LALU LINTAS (STUDI IZIN USAHA HOTEL DI KOTA DUMAI) - Melani "; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The rapid development of development in Dumai City is one of the characteristics of advanced cities, the more rapid development that occurs will lead to new problems that arise, namely the problem of traffic congestion and congestion, so the need for traffic impact analysis to answer the problems of rapid development, in Dumai City, the problem of traffic impact analysis has not been resolved because the Department of Transportation of Dumai City as an implementor has not been able to carry out and resolve problems regarding traffic impact analysis, all hotels in Dumai City do not have reliable permission, and there is also no active action from the Effectivieness problems that happened. The theory used in this study is the theory of George C. Edwards III's Policy Implementation, namely: (1) Achievement of Objectieves, (2) Integration, (3) Adaptation,. Qualitative descriptive research method. The informants in this study were 1 (one) Traffic Sector Executing Unit, 2 (two) developers / hotel parties who did not yet have an official permit. Data collection techniques in this study are by interview, observation (direct observation), literature study and documentation using purposive sampling method as a source of information and data analysis. The results of this study indicate that the operation is not reliable in Dumai City, due to lack of socialization and reliable information, there is no strict sanctions against hotel developers / businessmen regarding the issue of reliable permits.Keywords: Effectiveness, Organizing, Andal